Application of MTA to endodontic treatment of immature permanent teeth - Pels, Elżbieta; Tkacz-Ciebiera, Izabela; Błaszczak, Jerzy; Skawińska, Agnieszka; Mielnik-Błaszczak, Maria (Journal of Stomatology, 2015)
MTA (Mineral Trioxide Aggregate) is a new dental material of many clinical applications. MTA formulation is recommended for retrograde root filling, direct pulp capping, closing perforation resulting from the process of internal or external resorption, closing iatrogenic perforation, and in the apexification process as part of the final filling of the root canal in the periapical area. The aim of the study was to present physical and chemical properties and the use of MTA in the process of apexification and in the treatment of inflammatory periapical lesions in permanent immature teeth. Clinical examination revealed extensive damage to teeth 37 and 47 as a result of dental caries in a 12-year-old patient. Very deep carious lesions in these teeth resulted in necrosis of the pulp tissue and irreversible periapical inflammation. Endodontic treatment of immature permanent teeth was performed using formulations that initiate the process of apexification. Mineral Trioxide Aggregate (MTA) was used. It was found that MTA forms a good barrier ensuring the tightness of root canal filling. The material has a good antibacterial effect and satisfactory properties of enhancing the process of healing of inflammatory periapical lesions of immature teeth. The results of effective treatment of teeth with incomplete root formation require long-term studies for the objective assessment. MTA is a formulation with favourable properties and may seem a material of the future.